2018
DOI: 10.1007/s40333-018-0063-5
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of weeds and weed seeds in the soil by stubbles and no-tillage in an arid maize-winter wheat-common vetch rotation on the Loess Plateau of China

Abstract: Reduced tillage provides ecological and economic benefits to arable land on the Loess Plateau of China, where soil erosion has long been a serious problem and soil water availability is largely restricted. However, high abundances of weeds in reduced tillage systems cause significant yield losses. In this study, we explored the effects of no-tillage and stubble retention on the number and density of weeds and weed seeds in a 12-year maize-winter wheat-common vetch rotation on the Loess Plateau. Four treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…This study indicated that tillage was an effective measure to suppress the weed occurrence, especially in the early stages of wheat growth (Figures 1a and 2a), being consistent with previous researchers [14,47]. These findings could be primarily attributed to the disturbance of tillage burying weed seeds in the deep soil layer, decreasing the emergence of seedlings deriving from seeds [47].…”
Section: Impact Of Tillage and Crop Residue Management On Weed Speciesupporting
confidence: 91%
See 2 more Smart Citations
“…This study indicated that tillage was an effective measure to suppress the weed occurrence, especially in the early stages of wheat growth (Figures 1a and 2a), being consistent with previous researchers [14,47]. These findings could be primarily attributed to the disturbance of tillage burying weed seeds in the deep soil layer, decreasing the emergence of seedlings deriving from seeds [47].…”
Section: Impact Of Tillage and Crop Residue Management On Weed Speciesupporting
confidence: 91%
“…Agronomic practices can affect the weed flora and species composition of the weed community and soil seed bank in arable fields [7]. Crop rotation [8,9], fertilization [10][11][12][13], tillage [14][15][16], and crop residue retention [17][18][19] are effective measures to control weeds. No-till has been widely accepted in recent decades for many environmental benefits, such as reducing run-off, improving nutrient cycling, reducing soil degradation, decreasing water and soil pollution, and enhancing the activities of soil biota [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this time, we believe there are no research reports on the allelopathic effect of teff on different weed species. Most reports have focused on the allelopathic effect of certain plant species on teff [19,20,[35][36][37][38][39][40][41][42][43]. For example, leaf extracts from different eucalyptus species and Parthenium hysterophorus had an effect on the germination and early growth of teff [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…TCN is a unique farming method in the Southwest China purple soil region. It is a comprehensive farming method by gathering soil to build ridges and fertilizing in furrows (Liu et al 2013b;Liu and Huang 2013;Yang et al 2018;Niu et al 2019;Wang et al 2020a;Wang et al 2020c;Zhang et al 2020).…”
Section: Data Collectionmentioning
confidence: 99%